PERSERPSI MAHASISWA PENGENALAN LINGKUNGAN PERSEKOLAHAN (PLP) PPKN DALAM PENERAPAN PRINSIP KURIKULUM 2013 DI SMP NEGERI SE-KOTA PEKANBARU - Putri, Femmy Andani; Erlinda, Sri; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack : This research is motivated by the fact that since the implementation of the 2013 curriculum at all levels of education, both at the elementary school, junior high school to high school level, teachers and students introduced to the school environment have experienced many difficulties in applying the principles of the 2013 curriculum in schools. The formulation of the problem in this study is how students' perceptions of the introduction of the school environment PPKn in applying the principles of the 2013 curriculum in public junior high schools in Pekanbaru City. The purpose of this study was to determine students' perceptions of the introduction of the school environment PPKn on the application of the 2013 curriculum principles in public junior high schools in Pekanbaru City. The benefit of the results of this study is that it becomes a source of learning for all parties, especially for students who will take part in the school environment introduction program in schools, in order to understand more about the implementation of the 2013 curriculum in schools, so that its implementation is as expected. This research method is descriptive quantitative, data collection instruments used in this research are questionnaires and interviews which consist of one indicator with 14 questions. The population in this study were students introducing the school environment PPKn in public junior high schools in Pekanbaru City. The sample in this study was taken using a saturated sampling technique, where the population was directly sampled. Based on the results of the study, it was found that the result of the average percentage value of the alternative answers to the dominant respondents, namely those who answered “often” was 67.5%, where this range was in the “Good” category with an existence in the range of 50.01 - 75%. Thus it can be concluded that the students' perceptions of the introduction of the school environment PPKn in applying the principles of the 2013 Curriculum in Pekanbaru City public junior high schools is Good.Key Word : Perception, Curriculum-2013